Assessing the factors affecting SMEs' adoption of e-commerce in Kathmandu, Nepal - Jonchhe, Kaustubh; Ransom, Lakeesha K.; Badir, Yuosre; Kumar, Prashant; Asian Institute of Technology (2021)
Purpose- The purpose of this study is to analyze the factors that affect SMEs in Kathmandu, Nepal to adopt ecommerce in their business. Methodology- Questionnaires were distributed amongst the SMEs based in Kathmandu valley via Google forms. A total of 170 responds was collected, out of which 3 respondents were dropped because they had not adopted ecommerce yet. A series of analysis and test were run on this data. Findings- Results from the data showed positive outcomes for all the independent variables relative advantage, competitive pressure, IT readiness, organizational performance and perceived usefulness being a factor for adopting ecommerce. However, the findings also showed that there was no link between the moderating variable and independent variable. Implications- The study suggests the owners, or the managers of SMEs based in Nepal the benefits of adopting ecommerce. Similarly, the study also suggests that managers and owners should educate the employees about the techniques to use ecommerce in their platform.
A research submitted in partial fulfillment of the requirements for the degree of Master of Business Administration
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2021
Keywords: Small business -- Nepal -- Kathmandu; Electronic commerce -- Nepal -- Kathmandu